1992
DOI: 10.1111/j.1365-2796.1992.tb00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between the apolipoprotein B gene 3‘ hypervariable region alleles and coronary artery disease in Finnish patients with angiographically documented coronary artery disease

Abstract: Previous studies have suggested that some apolipoprotein B (apoB) 3' variable number of tandem repeats (3'VNTR) locus alleles are associated with coronary artery disease (CAD). We examined the possible association between the apoB 3'VNTR alleles and CAD in 387 Finnish subjects. Using the polymerase chain reaction and polyacrylamide gel electrophoresis, the 3'VNTR genotype was determined in 187 individuals with severe CAD confirmed by coronary angiography (patients), in 121 individuals with normal coronary angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In a previous study, however, Hegele et al [45] found a significant correlation between Apo B gene polymorphisms and CHD, without any significant association with either LDL or VLDL. There was also no significant association between the 3'VNTR alleles and serum lipid levels in the Finnish population [31]. Similar results were reported in a porcine model of atherosclerosis in which an Apo B genetic variant was associated with atherosclerosis, despite normal lipid levels [46].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In a previous study, however, Hegele et al [45] found a significant correlation between Apo B gene polymorphisms and CHD, without any significant association with either LDL or VLDL. There was also no significant association between the 3'VNTR alleles and serum lipid levels in the Finnish population [31]. Similar results were reported in a porcine model of atherosclerosis in which an Apo B genetic variant was associated with atherosclerosis, despite normal lipid levels [46].…”
Section: Discussionsupporting
confidence: 54%
“…Numerous polymorphisms of the Apo B gene have been described. Particularly, a variable number of tandem repeats (VNTR) polymorphism, which is located 75 bp downstream the second polyadenylation signal at the 3' end of the Apo B gene (2p24-p23) has been found to be common in some ethnic groups [18-21], and it has been reported to be associated with modifications of lipid concentrations [22-28] and the risk of CHD [25-30] in some studies but not in others [31,32]. …”
Section: Introductionmentioning
confidence: 99%
“…As a highly polymorphic genetic marker, the APOB gene 39VNTR is a powerful tool for different studies, including genome mapping, linkage analysis, forensic and paternity identification, anthropological research, phylogenetic and epidemiological studies (4)(5)(6)(7)(13)(14)(15)(16)(17)(18). Two basic types of 15-nucleotide-long core repeats (X and Y) have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The APOB 39VNTR polymorphism can be analyzed by polymerase chain reaction (PCR) amplification and high-resolution agarose (8) or polyacrylamide gel or capillary electrophoresis (9)(10)(11). This polymorphism was reported to be associated with altered lipid levels (12,13) and/or risk of atherosclerosis and coronary heart disease (CHD) (13,14), while other similar studies showed conflicting results (15)(16)(17), although the underlying mechanism remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…They were associated with modifi cations of lipid concentrations (267)(268)(269)(270)(271) and the risk of coronary heart diseases ( 270-272 ). Nevertheless, not one of these associations has been consistently observed in a large number of studies ( 273,274 ). Discrepancies may be related to differences of ethnic groups and environmental factors.…”
Section: Discussionmentioning
confidence: 99%